Tinjauan Kriminologis terhadap Faktor Penyebab Overkriminalisasi di Indonesia dalam Perspektif Reformasi Hukum - Dewayanti Tomayahu; Nabila Putri Isabel Yahya; Roy Marthen Moonti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon of overcriminalization in Indonesia reflects the excessive use of criminal law against actions that should not be classified as crimes. This study aims to identify the criminogenic factors behind overcriminalization and to evaluate the urgency of reforming criminal policy. Using a normative-juridical and criminological approach, the research reveals that overcriminalization is driven by ambiguous legal norms, weak law enforcement capacity, cultural bias, and the lack of restorative justice mechanisms. As a result, vulnerable groups—such as minors, youth drug users, and the economically disadvantaged—are often subjected to disproportionate criminalization. The study concludes that the criminal justice system must return to the principle of ultimum remedium. A comprehensive legal reform is recommended through interdisciplinary methods, inclusive public participation in legislation, and the strengthening of humanistic and contextual legal education.